Biaxial Mechanochromic Behaviors of Mechanically Heterogeneous Colloidal Photonic Crystal Weave - Cho, Youngki; Oh, Chi Yeung; Son, Eun Ji; Kim, Young Seok; Shim, Tae Soup (Advanced Optical Materials, 2024)
Non-close-packed colloidal photonic crystals (CPhCs) are widely employed in biomimetic strain sensors as they exhibit mechanochromism due to changes in the crystal lattice spacing under stress. However, the structural color of a CPhC film with an incompressible polymer matrix changes with modulation of the film thickness due to deformation, which makes it difficult to visualize the magnitude and direction of the stress. To address this limitation, elastic modulus-controlled CPhC films with stress-responsive mechanochromic behavior are fabricated. While each CPhC film shows the same color change under constant strain, the color change is controlled differently under constant stress. Combining CPhC films prepared with different modulus values enhanced the strain-responsive mechanochromic sensitivity by ≈25 times. A mechanically heterogeneous weave structure demonstrates a unique biaxial mechanochromic response based on the direction of the stress. These findings suggest that CPhC films can serve as versatile strain/stress sensors that provide visual information about the magnitude and direction of applied stress in multiple dimensions.
Keywords: Close packed; Colloidal photonic crystals; Color changes; Core-shell nanoparticles; Lattice spacing; Mechanochromic; Melt-shear assembly; Photonic crystal films; Strain sensors; Structural color; colloidal photonic crystals; core-shell nanoparticles; mechanochromic; melt-shear assembly; strain sensors